Acessibilidade projetada e acessibilidade real: avaliação com base no retorno de experiência de pessoas com deficiência - Igor dos Santos (2018)
The contribution of the engineer in his projects needs to integrate the dialogue and the experience of the user. Existing structures that aim to promote effective accessibility for people with disabilities are still precarious, even with the efforts of legislators and universal design experts, even in urban spaces designed or reformed for this purpose. Starting from the idea of a project promoted by an NGO (here called the Institute), which was given the mission to insert people with disabilities in places of leisure and fun through a social project (here called Movement), we investigated how a social technology and a festival could reach that goal. This research used an exploratory methodological approach that combined ergonomics to conception, research-action and Grounded Theory, allowing the researcher's immersion in the development of a social project by the Institute, showing how the process of ideation of an innovation social situation faces several uncertainties, as well as in the day-to-day of the target public of the project, especially in its activity of moving through the urban environment. Professionals and people with disabilities were interviewed. The qualitative analysis analyzed the physical barriers that impede the insertion of people with disabilities in places of social coexistence. In this context, the notion of "real accessibility" emerged as the study of the practical relation of an individual to the urban environment and the forms of accessibility that are presupposed in reality. The information collected and systematized provided recommendations for the technology suggested by the Institute, analyzed here, so that people with mobility problems become protagonists in helping others to be more active in public places. In addition, it also provided the study of the return of experience (REX) evaluation method, a methodological strategy that can contribute to the good practices of studying the relationship between person and the environment, such as post-occupation evaluation (APO), to capture the real needs of users